A multilevel test of the racial threat hypothesis in one state’s juvenile court - Lowery, Patrick G. (Crime & delinquency, 2018)
Noting the paucity of research on the racial threat hypothesis in the juvenile courts, this study examined the interplay of defendant characteristics and country-level characteristics on dispositions. Data were retrieved from the Department of Juvenile Justice files in South Carolina and were analyzed using multinomial logistic hierarchical linear modeling. Results revealed support for the racial threat hypothesis, as racial inequity operated in a different manner (more punitively) for Black defendants. Larger Black populations in counties also led to an increased use of punitive sanctions. In addition, concentrated disadvantage effects were found, and heightened levels of teenage population led to higher incarceration rates for Black defendants. Limitations of this study, implications for stakeholders/practitioners, and directions for future research are discussed.